Cesarean section trend: A reflection from ethics - Vanegas López, Jairo Javier; Pávez Lizárraga, Amaya; Muñoz Ojeda, Patricia (Acta Bioethica, 2021)
World statistics show an upward trend in Cesarean section rates that exceed the 15% recommended by PAHO / WHO. This surgery has become the most common in high- and middle-income countries. Some studies suggest that not all these caesarean sections would be justified. In this regard, some reflections are made on the ethical dilemmas that can be observed from various theoretical positions such as consequentialism, Kantianism, the ethics of virtue and feminist theory. In turn, these dilemmas are immersed in multiple individuals, social and cultural factors, among others. From Public Health, the current parameter defined as the “acceptable range” of Caesarean sections should be reviewed as it may be too low. It is also recommended that measures be applied to strengthen patients' desire for a normal delivery whenever possible through timely information and education during prenatal care. The decisions of the health professional and women must be supported by the best information available.